Milk or wine: Mutual funds' (dis)economies of life - Laura K. Dahm; Christoph Sorhage (University of Cologne, Centre for Financial Research (CFR), 2015)
Mutual fund investors are supposed to make long-term investments instead of striving for quick fortunes. However, the dynamics of funds' ability to generate abnormal returns over their lifetime is still an unattended issue. This paper provides evidence on the liability of newness and liability of aging theory that funds' investment skill changes to the positive or negative over time. Our results find strong support for an underperformance of mature funds consistent with the liability of aging theory. Furthermore, the observed diseconomies of life result from older funds pursuing less innovative investment strategies. The lack of innovation manifests in less performance enhancing trading and fewer investments in hard-to-value stocks. Still, we provide evidence that less performance sensitive as well as non-institutional investors seek investments in mature funds and that they benefit from more stable investment styles and performance outcomes.
Keywords: D22; D23; D92; G11; G23; L25; 330; Mutual funds; Fund age; Innovation; Liability of aging; Fund performance; Fund behavior